Handbook of research on strategic management for current energy investments - Yuksel, Serhat, 1983-; Dinçer, Hasan, 1982- (Engineering Science Reference, 2022)
"This book analyzes current trends in energy production and use, discussing technological developments that contribute to the reduction of price in energy production and renewable energy sources that provide continuity in energy production"--